2017
DOI: 10.4103/1119-3077.181399
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil lymphocyte ratio predicts postoperative pain after orthognathic surgery

Abstract: Preoperatively measured NLR may help to predict postoperative analgesic demand in patients undergoing orthognathic surgery, and thus sufficient postoperative pain control can be achieved with various preventive treatments taken at the perioperative period such as preemptive analgesia, local anesthetic administration at the end of surgery, or early administration of analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 2 publications
0
22
0
1
Order By: Relevance
“…The pain is related to the surgical act itself and several factors, such as contraction of peripheral soft tissues and surrounding muscle stiffness (26) . Its control improves respiratory function, promotes hemodynamic stability, inhibits hormonal and metabolic reactions, and decreases hospitalization time (27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain is related to the surgical act itself and several factors, such as contraction of peripheral soft tissues and surrounding muscle stiffness (26) . Its control improves respiratory function, promotes hemodynamic stability, inhibits hormonal and metabolic reactions, and decreases hospitalization time (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Another topic was about the medications used. Opioids are used to treat pain in the immediate postoperative period, while traditional analgesics are used in the mediate period (26) . However, the administration of non-steroidal anti-inflammatory drugs is also frequently employed, depending on the patient's pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a higher NLR is positively related to high mortality, poor prognosis, inflammatory status, and its consequences. It is well-known that NLR is a potential biological marker of inflammation in several diseases and can be a useful predictive tool for post-operative pain resulted from inflammatory pathways secondary to surgical trauma [20], [21], [22]. NLR is an easily calculated and inexpensive marker in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Turgut et al [22] retrospectively evaluated the predictive role of pre-operative NLR and post-operative pain in 140 patients who underwent orthognathic surgery. They reported that the analgesic demand with NLR ≥2 correlates with increased post-operative pain, which is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatif dönemde NLO≥2 olarak hesaplanan hastalarda, postoperatif analjezik gereksiniminin daha fazla olduğu belirlenmiştir. 22 Çalışmamızda da bu sonuçlara benzer olarak, preoperatif dönemde NLO >2 olan hastalarda portoperatif dönemde VAS değerleri daha fazla bulunmuşve toplam analjezik süresi de daha kısa hesaplanmıştır.…”
Section: Tartişma Ve Sonuçunclassified